2015
DOI: 10.1021/ja508371q
|View full text |Cite
|
Sign up to set email alerts
|

Amine Oxidative N-Dealkylation via Cupric Hydroperoxide Cu-OOH Homolytic Cleavage Followed by Site-Specific Fenton Chemistry

Abstract: Copper(II)-hydroperoxide species are significant intermediates in processes such as fuel cells and (bio)chemical oxidations, all involving stepwise reduction of molecular oxygen. We previously reported a CuII-OOH species that performs oxidative N-dealkylation on a dibenzylamino group that is appended to the 6-position of a pyridyl donor of a tripodal tetradentate ligand. To obtain insights into the mechanism of this process, reaction kinetics and products were determined employing ligand substrates with variou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
88
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9
1

Relationship

4
6

Authors

Journals

citations
Cited by 102 publications
(91 citation statements)
references
References 69 publications
3
88
0
Order By: Relevance
“…4A, Left) is initial protonation of the proximal O to the hydrogen peroxide complex Cu II M -OðHÞOH (reaction b; ΔG = +8.7 kcal/mol) followed by ET from Cu H (reaction c; ΔG = -9.5 kcal/mol). This would generate H 2 O 2 in the presence of Cu I , which is known experimentally to lead to Fenton chemistry via homolytic O-O cleavage and release of • OH (12). Indeed, O-O cleavage in Cu I M -OðHÞOH to produce • OH would be thermodynamically accessible in PHM with calculated ΔG = -2.2 kcal/mol ( Fig.…”
Section: Rebound To the Protonated Versus Nonprotonated Oxygen Of Cumentioning
confidence: 97%
“…4A, Left) is initial protonation of the proximal O to the hydrogen peroxide complex Cu II M -OðHÞOH (reaction b; ΔG = +8.7 kcal/mol) followed by ET from Cu H (reaction c; ΔG = -9.5 kcal/mol). This would generate H 2 O 2 in the presence of Cu I , which is known experimentally to lead to Fenton chemistry via homolytic O-O cleavage and release of • OH (12). Indeed, O-O cleavage in Cu I M -OðHÞOH to produce • OH would be thermodynamically accessible in PHM with calculated ΔG = -2.2 kcal/mol ( Fig.…”
Section: Rebound To the Protonated Versus Nonprotonated Oxygen Of Cumentioning
confidence: 97%
“…N-dealkylation reactions of complexes ( 27 ) of L41g (R = H) and L41i – k (R = aryl) (refs 182, 186, and 189). …”
Section: Figurementioning
confidence: 99%
“…Model complex chemistry was reported using 6-[bis(phenylmethyl)amino]- N , N -bis(2-pyridinylmethyl)-2-pyridinemethanamine derivatives as ligands to Cu(I). 273 Reaction of the Cu(I) complex with H 2 O 2 formed a Cu(I)–OOH complex that can be protonated at either the proximal nonprotonated or the distal protonated O of the hydroperoxy moiety (Figure 33A). DFT calculations showed that distal protonation of the Cu(I)–OOH to yield a Cu(II)–oxyl species is thermodynamically more favorable than protonation at the proximal oxygen.…”
Section: Active Site Geometric and Electronic Structure And Molecumentioning
confidence: 99%